An experimental investigation of liquid CO2-in-water emulsions for improving oil recovery. (15th March 2021) - Wu, Xidao; Zhang, Yu; Zhang, Ke; Liu, Bei; Zuo, Julian Y.; Chen, Guangjin; Xiao, Peng
Abstract: Dissolving CO2 in crude oil results in a significant oil viscosity reduction, but CO2 injection suffers from poor sweep efficiency because of high CO2 mobility. In this study, the emulsions by mixing liquid CO2 with water was made to enhance oil recovery (EOR) by means of reducing CO2 mobility. The morphology and stability of different CO2 emulsions were investigated. The results suggested that a liquid CO2 -in-water (C/W) emulsion stabilized by alkyl polyglycoside (APG) was generated at 299.15 K; and the emulsion with water cut of 30 vol% and APG concentration of 3.0 wt% exhibited the optimal stability which was applied in slim tube experiments. Compared with pure CO2, the higher density and viscosity of the C/W emulsion at ambient temperature implied a lower CO2 mobility in displacement. In the slim tube experiments, the displacement results of CO2 injection and C/W emulsion injection were compared and discussed at 363.15 K, and two crude oils were used to study the effect of crude oil properties on oil recovery. Up to 15% of additional oil recovery was obtained by the C/W emulsion flooding compared with the pure CO2 injection at 13 MPa and 363.15 K and it decreased with increasing pressure. Meanwhile, the differential pressure behavior and displacement velocity across the slim tube suggested that the C/W emulsion could have a lower relative permeability and decreased CO2 mobility in porous media. There was an interesting discovery that emulsification of crude oil could be an instrumental factor of the C/W emulsion in EOR. Furthermore, the flooding results of two crude oils indicated that the C/W emulsion injection has a better performance for the heavier crude oil in the slim tube experiments. The enhanced oil recovery suggested that the C/W emulsion could be a potential EOR method for heavy crude oil reservoirs.